Developing educational planning competence in the bachelor's degree in Education - Gina Chianese; Matteo Cornacchia (Firenze University Press, 2020)
The purpose of the paper is to analyze the ways through the which the study courses in Education and Training Sciences develop the educational planning competence, recognized by the TECO project as one of the six final training objectives of the L-19 degree class. The educational planning competence is recognized as key condition in educational work and more than other, it assumes in itself the paradigm of the complexity in taking into account constraints and resources, opportunities and risks. Since the development of competences implies experiential and pro-active approaches, the academic courses engaged in the training of educational figures must be able to connect the academic know-how and theories (disciplinary contents) to the learning in situation/context (apprenticeship and laboratories), to extra-curricular learning and experiences that, through informal channel/dimension, contribute to the development of the transversal competences and the professional habitus.   Sviluppare la competenza progettuale nel lavoro educativo all'interno dei corsi di studio in Scienze dell'educazione e della formazione Scopo del contributo è analizzare le modalità attraverso cui i corsi di studio in Scienze dell'educazione e della formazione sviluppano la competenza progettuale, riconosciuta dal progetto TECO uno dei sei obiettivi formativi finali della classe di laurea L-19. La capacità di progettare viene riconosciuta fra le condizioni fondative del lavoro educativo e più di altre, assume in sé il paradigma della complessità, nella misura in cui devono essere considerati vincoli e risorse, opportunità e rischi. Dal momento che la formazione delle competenze (non solo progettuali) presuppone approcci esperienziali e proattivi, i percorsi universitari che preparano le professioni educative devono essere in grado di coniugare il sapere propriamente accademico (gli insegnamenti disciplinari) con spazi di apprendimento in situazione (tirocinio e laboratori) e spazi di apprendimento extracurricolare che, attraverso il canale dell'informale, contribuiscono alla costruzione delle competenze trasversali e degli abiti professionali.